Discovery and Validation of Ferroptosis-Associated Genes of Ulcerative Colitis - Zhu J; Wu Y; Ge X; Chen X; Mei Q (Dove Medical Press, 2024)
Jiejie Zhu,1,2 Yumei Wu,1,2 Xiaoyuan Ge,1,2 Xinwen Chen,1,2 Qiao Mei1,2 1Department of Gastroenterology, The First Affiliated Hospital of Anhui Medical University, Hefei City, Anhui Province, People's Republic of China; 2Key Laboratory of Digestive Diseases of Anhui Province, Hefei, People's Republic of ChinaCorrespondence: Qiao Mei, The First Affiliated Hospital of Anhui Medical University, 218 Jixi Road, Hefei, Anhui Province, 230022, People's Republic of China, Email meiqiao@hotmail.comBackground: Ulcerative colitis (UC) is a long-lasting idiopathic condition, but its precise mechanisms remain unclear. Meanwhile, evidence has demonstrated that ferroptosis seems to interlock with the progress of UC. This research sought to identify hub genes of UC related to ferroptosis.Methods: First, the relevant profiles for this article were obtained from GEO database. From the FerrDb, 479 genes linked to ferroptosis were retrieved. Using analysis of the difference and WGCNA on colonic samples from GSE73661, the remaining six hub genes linked to ferroptosis and UC were discovered. Through logistic regression analyses, the diagnostic model was constructed and was then evaluated by external validation using dataset GSE92415. Afterwards, the correlation between immune cell filtration in UC and hub genes was examined. Finally, a mice model of colitis was established, and the results were verified using qRT-PCR.Results: We acquired six hub genes linked to ferroptosis and UC. In order to create a diagnostic model for UC, we used logistic regression analysis to screen three of the six ferroptosis related genes (HIF1A, SLC7A11, and LPIN1). The ROC curve showed that the three hub genes had outstanding potential for disease diagnosis (AUC = 0.976), which was subsequently validated in samples from GSE92415 (AUC = 0.962) and blood samples from GSE3365 (AUC = 0.847) and GSE94648 (AUC = 0.769). These genes might be crucial for UC immunity based upon the results on the immune system. Furthermore, mouse samples examined using qRT-PCR also verified our findings.Conclusion: In conclusion, the findings have important implications for ferroptosis and UC, and these hub genes may also offer fresh perspectives on the aetiology and therapeutic approaches of UC.Keywords: ulcerative colitis, ferroptosis, hub genes, immune, bioinformatics analysis